Phase I/II Study of Weekly Oraxol for the Second‐Line Treatment of Patients With Metastatic or Recurrent Gastric Cancer. (25th June 2015) - Lee, Keun‐Wook; Lee, Kyung Hee; Zang, Dae Young; Park, Young Iee; Shin, Dong Bok; Kim, Jin Won; Im, Seock‐Ah; Koh, Sung Ae; Yu, Kyung‐Sang; Cho, Joo‐Youn; Jung, Jin‐A; Bang, Yung‐Jue
Abstract : Lessons Learned: Oraxol, a novel oral formulation of paclitaxel, displayed modest efficacy as second‐line chemotherapy for gastric cancer. Considering its favorable toxicity profiles, further studies are warranted in various solid tumors including gastric cancer. Background: Oraxol consists of paclitaxel and HM30181A, a P‐glycoprotein inhibitor, to increase the oral bioavailability of paclitaxel. This phase I/II study (HM‐OXL‐201) was conducted to determine the maximum tolerated dose (MTD) and recommended phase II dose (RP2D) of Oraxol. In addition, we investigated the efficacy and safety of Oraxol as second‐line chemotherapy for metastatic or recurrent gastric cancer (GC). Methods: In the phase I component, paclitaxel was orally administered at escalating doses (90, 120, or 150 mg/m 2 per day) with a fixed dose (15 mg/day) of HM30181A. Oraxol was administrated 6 times per cycle (days 1, 2, 8, 9, 15, and 16) every 4 weeks. In the phase II component, the efficacy and safety of Oraxol were evaluated. Results: In the phase I component, the MTD could not be determined. Based on toxicity and pharmacokinetic data, the RP2D of oral paclitaxel was determined to be 150 mg/m 2 . In the phase II component, 4 of 43 patients (9.3%) achieved partial responses. Median progression‐free survival and overall survival were 2.6 and 10.7 months, respectively. Toxicity profiles were favorable, and the most common drug‐related adverse events (grade ≥3) were neutropenia and diarrhea. Conclusion: Oraxol exhibited modest efficacy and favorable toxicity profiles as second‐line chemotherapy for GC. Abstract : 摘要 背景 . Oraxol由紫杉醇和HM30181A(一种P糖蛋白抑制剂, 可增加紫杉醇的口服生物利用度)组成。本项I期/II期研究(HM‐OXL‐201)旨在确定Oraxol的最大耐受剂量(MTD)和II期推荐研究剂量(RP2D)。此外, 我们还对Oraxol用于转移性或复发性胃癌(GC)二线化疗的有效性和安全性进行了研究。 方法 . 在I期研究阶段, 紫杉醇经口服给药且剂量逐渐提升(90、120和150 mg/m 2 /天), HM30181A按固定剂量给药(15 mg/天)。Oraxol每周期给药6次(第1、2、8、9、15和16天), 每4周为一周期。在II期研究阶段评价Oraxol的有效性和安全性。 结果 . I期研究阶段未能确定MTD。依据毒性和药代动力学数据, 确定口服紫杉醇的RP2D为150 mg/m 2 。在II期研究阶段, 4/43例患者(9.3%)达到部分缓解。中位无进展生存和总生存分别为2.6个月和10.7个月。毒性特征谱良好, 最常见的药物相关不良事件(≥ 3级)为中性粒细胞减少症和腹泻。 结论 . Oraxol用于胃癌二线化疗时表现出一定的有效性和良好的毒性特征谱。 The Oncologist 2015;20:896–897